The book of three - Alexander, Lloyd (New York : H. Holt, 1999)
Taran, Assistant Pig-Keeper to a famous oracular sow, sets out on a hazardous mission to save Prydain from the forces of evil.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
4.8.
4.8
5-8
Keywords: Fantasy; Fantasy